GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEPUASAN KERJA GURU DI TAMAN KANAK-KANAK UPTD KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE. - Listiyawati, Murniati AR, Niswanto. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: This study aims to determine of work programof teachingsupervision, implementationsupervisionof teaching, andthe principalconstraintsin implementation ofthe teachingsupervision. To achieve these objectives, this study uses a qualitative approach. Data was collected through interviews, observation, and documentation. The results showed that: (1) Style of principal leadership in improving job satisfaction of teachers (2) Strategy pricipals in improving job satisfaction and (3) Constraints faced by principals in improving job satisfaction of teachers, among others: (a) the principal has not fully have the mindset intact as a leader of the institution/organization and so it is not appropriate to use the style of leadership, (b) the teachers have not fully understand and internalize its performance in the learning process so that the impact to job satisfaction, means a game which is owned by the school so that the activity of children's play is not controlled, and (c) the lack of facilities and teaching materials that are owned by the school so that learning takes place following the rules laid down by foundations and impact to the job satisfaction of teachers..Keywords: Leadership Style and Job Satisfaction of Teachers.Abstrak: Gaya kepemimpinan yang diterapkan oleh sejumlah orang memberi pengaruh yang signifikan terhadap prseoramgan atau kelompok, sehimgga dengan penuh kesadaran orang-orang tersebut mengikuti apa-apa yang diinginkan pemimoin dalam mencapai tujuan. Adapun kepuasan kerja selalu menjadi ukuran terhadap diri seseorang atau kelompok terhadap prestasi kerja yang dihasilkan. Penelitian ini bertujuan untuk mengtahui (1)Gaya kepemimpinan keala sekolah,(2) strategi kepala sekolah dan (3) kendala yang dihadapai kepala sekolah terhadap kepuasan kerja guru pada Taman Kanak-Kanak UPTD Kecamatan Banda Sakti Kota Lhokseumawe. Penelitian ini menggunakan pendekata kualitatif denf\gan tekhnik pengumpulan data melalui  observasi wawancaradan study dokumtasi dengan subjek peneliutian kepala sekolah da guru. Hasil penelitian menunjukan bahwa: a. gaya kepemimpian kepala sekolah terhadap kepuasan kerja guru memiliki beberapa perbedaan. b. para guru belum sepenuhm\nya memahami proses pembelajaran sehingga berdampak kepada kepuasan kerja. c. sedikitnya bahan ajar yang dimilii sekolah sehingga pembelajaran berlangsung mengikuti aturan yang diterapkan oleh yayasan.Kata Kunci : Gaya Kepemimpinan dan Kepuasan Kerja Guru.